European startups in the Chinese market: what are the first important steps? - Lenteren, Eva Chloé van (2018)
In this thesis, which I write as a final work for the master in Chinese Studies at the University of Aveiro, I will research Portuguese Startup companies, the interest they have in entering the Chinese market and the difficulties they might come across when doing so. I will investigate their investment vehicle, their product and the barriers they have setting up their company and negotiating with the Chinese. I will make a questionnaire to obtain the right information and will draw my conclusions after having investigated these issues. I will try to come up with a plan to help them and to see how they can be facilitated with overbridging language and culture differences. And how I specifically, can help with the knowledge gained throughout my studies